Proposition and application of a method for the characterization of rural areas in the census sectors from the sanitation point of view - Pinheiro, Roberta Vieira Nunes; Chagas, Isabela Moura; Basso, Reviel Eurico; Nóbrega, Juliana Dorn; Bezerra, Nolan Ribeiro; Scalize, Paulo Sergio (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2022)
Considering the concept of rurality, the need for methods to contextualize the rural areas and the attendance by sanitation services, the goal of this work was to propose and apply a method of characterization in census sectors (CS) of rural areas. For such, a classification method for rural clusters was built, considering the selected criteria based on the Programa Saneamento Brasil Rural (Rural Brazil Sanitation Program) and other technical-scientific literature. The method encompassed three criteria: the identification of clusters and dispersed households, distance from the cluster to the closest urban center (Cucd) and demographic density (Dd). Of all the 115 rural areas in the state of Goiás, it was possible to apply such in 98, as in the remaining 17 the method could not be directly applied, due to the existence of one or more clusters with the presence of households that do not make part of the rural area, that is, non-contiguous households. In a more detailed analysis, four areas were identified where the method could be applied to a group of households. A total of 103 rural areas were numbered, with an average Cucd of 27.7km (SD = 19.42; CV = 0.70), and average Dd of 50.1 inhabitants per square kilometer, in which 118 clusters were detected. Of that total, 6.79% were classified in the CS 1b and 2, 7.77% on 3 and 85.44% on 5 and 7. It was concluded that the method can be applied integrally in a rural area and/or clusters with contiguous households. Lastly, the classification in CS allows for a preliminary analysis of solution propositions for basic sanitation, being them collective and/or individual, centralized and/or decentralized, according to spacial technical criteria.